Oil Price Fluctuation and Firm Performance in Developing Economy: Evidence from Oman - Bilal, Zaroug Osman; Mohammed, Shariq; Ali, Yassir Yaqoub (International Journal of Energy Economics and Policy, 2021)
The study aims to investigate how oil continues to be the driving force of the Omani economy. Accordingly, changes in oil prices will have positive or negative impacts on all economic sectors. This study investigates the impact of oil prices on firm performance in 74 industrial and services companies listed on the Muscat Stock Exchange (MSM) from the years 2010 to 2018.This study's econometric model uses panel data regression since comprising time-series and cross-sectional data. The paper examines the effects of oil price fluctuations on the sampled firms' performance. The statistical analysis indicates that oil prices have a significant positive impact on financial performance (as measured by return on assets - ROA) with the exception of the interest rate. Moreover, all fixed effects are highly significant for the five sectors. This result contributes to the literature by highlighting the impact of oil price on firm performance in Oman's industrial and service sectors. Both sectors are highly exposed and sensitive to oil price fluctuations. All regression coefficients in all sectors are highly significant, with the exception of interest rate, which has no impact on the profitability performance of the cement, oil, and textile industries. Moreover, both fixed and effects models are highly significant. Keywords: Oil price, Firm performance, ROA, panel data, industrial and service sectors, Oman. JEL Classifications: E44, F31, F37, B25 DOI: https://doi.org/10.32479/ijeep.10990